Preserving Indonesian Traditional Music through Copyright Protection and Government Intervention - Harliani, Eni; Fuad, Fokky; Machmud, Aris (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2025)
Traditional Indonesian music faces significant challenges in the digital era, particularly regarding unauthorized use and copyright protection. This study examines the Indonesian government’s role in protecting traditional music copyright through a normative legal approach. The research reveals that the government has implemented several key strategies: establishing a comprehensive legal framework through Law No. 28/2014 on Copyright and related regulations; facilitating the creation of Collective Management Institutions (CMIs) for traditional music, including the successful establishment of three integrated CMIs in 2023; conducting public awareness campaigns and education programs across various regions; and strengthening law enforcement against copyright infringement. Despite these efforts, challenges persist, including limited public awareness of legal protections, unauthorized commercial use, and enforcement difficulties. The study concludes that continued government involvement, particularly in education and law enforcement, is crucial for preserving Indonesia’s traditional musical heritage.